PENTINGNYA SERTIFIKASI HALAL BAGI UMKM DALAM MENGHADAPI PASAR GLOBAL PADA IBU SUSWANTI - Mhd. Johan; Didi Yunaspi; Gaguk Rudianto; Winda Evyanto; Zia Hisni Mubarak; Yunisa Oktavia; Robby Satria (ASOSIASI IDEBAHASA KEPRI, 2026)
The purpose of this community service is to facilitate business actors in obtaining halal certification easily. In addition, to increase income for UMKM/MSMEs (micro, small, and medium enterprises) in Indonesia, especially Batam. Then the government provides comfort to all consumers in consuming food sold by business actors. After that, the government protects the Indonesian people, especially Muslims, in consuming food sold by traders both on the streets and in traditional markets. In these matters, business actors need assistance to obtain halal certification, because not all business actors can understand the existing administration in halal. Then to obtain NIB, business actors must be assisted, because many things are unknown in making NIB. NIB is something that is mandatory to obtain halal certification. The method used to process this is an interview method between the business mentor and the business actor. Here the business mentor tries to obtain information owned by the business actor. The results obtained, the business actor successfully obtained a halal certificate as a requirement to sell its products at Alfamart and One Mall Batam.